2017
DOI: 10.15560/13.6.993
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of drifting juvenile seahorse Hippocampus trimaculatus (Leach, 1814) beneath the offshore surface at Malacca Strait

Abstract: Three drifting juvenile seahorses (100.3 mm, 89.5 mm, and 55.8 mm in height) were captured during 2 research surveys between shipping routes at Malacca Strait. All seahorse specimens were identified using morphometric data as Hippocampus trimaculatus Leach, 1814. This is the first direct observation of drifting H. trimaculatus seahorse near to the water surface, out of their reported water depth (10-100 m) and demersal habitats. This may provide evidence of translocation and long-distance dispersal of H. trima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Since the H:S ratio in this study was also similar to that reported in H. kuda adults (Lourie et al, 2004;Choo and Liew, 2006), it reaffirms the ratio as being species-specific. These morphometric data could aid in the conservation management and identification of wild drifting seahorse species at juvenile stages (Vincent et al, 2011;Luzzatto et al, 2013;Wong and Teh, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Since the H:S ratio in this study was also similar to that reported in H. kuda adults (Lourie et al, 2004;Choo and Liew, 2006), it reaffirms the ratio as being species-specific. These morphometric data could aid in the conservation management and identification of wild drifting seahorse species at juvenile stages (Vincent et al, 2011;Luzzatto et al, 2013;Wong and Teh, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Sand bottom is the preferable habitat for these species, with H. spinosissimus commonly associated with soft corals (Lim et al, 2011;Shapawi et al, 2015). In 2017, H. trimaculatus was observed drifting near the water surface of Port Dickson (Negeri Sembilan), indicating translocation and long-distance dispersal from deeper areas and demersal habitats (Wong and Teh, 2017).…”
Section: Habitat and Distribution Of Seahorses In Malaysiamentioning
confidence: 99%
“…Since then, aquaculture has been developed to ensure the sustainability of the seahorse trade (Job, 2005). VU Liew (2003, 2004), Lim et al (2011), Wong and Teh (2017) IUCN status: LC = Least concern, DD = Data deficient, VU = Vulnerable Morphology description referring to Lourie et al (2004), Lourie and Kuiter (2008) The proportion of cultured seahorses in the aquarium trade increased rapidly after their listing in CITES. However, the industry is still struggling to produce adequate numbers of juveniles for farming.…”
Section: Conservationmentioning
confidence: 99%
See 1 more Smart Citation